Peningkatan Kemandirian dan Prestasi Belajar IPA melalui Problem Based Learning berbantuan Lembar Kerja Siswa - Hartini, Hartini (Paedagogie, 2019)
This study aimed to improve students' self-independence and learning achievement through Problem Based Learning (PBL) assisted with problem-based worksheets. This action research was conducted in VIID class of the State Junior High School 1 of Karangkobar in the second semester of Academic Year of 2017/2018. It was conducted through 2 cycles. Data was gathered through observation and test. Students’ self-independence raised from pre cycle (13.02), cycle I (17,09), and to cycle II (20.02). While the average science achievement score raised from the pre-cycle (62.90), cycle I (77.47), and to cycle II (80.06). Thus, Problem Base Learning Model (PBL) assisted with problem-based worksheets could improve students’ self-independence and science achievement.